2012
DOI: 10.1002/marc.201200005
|View full text |Cite
|
Sign up to set email alerts
|

Development of Star Polymers as Unimolecular Containers for Nanomaterials

Abstract: Star polymers containing one central core surrounded by multiple radiating arms represent an intriguing type of globular platform to be used as unimolecular containers and reactors. The core domain can encapsulate guest "cargos", whereas protective shell and chain ends can be functionalized with reactive groups and ligands. This Feature Article highlights the recent development on using core-shell structured amphiphilic star polymers as unimolecular containers for applications in drug delivery, catalysis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
152
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 145 publications
(177 reference statements)
0
152
0
Order By: Relevance
“…In the "corefirst" approach, polymeric arms are grown from a multifunctional cross-linked initiator, while in the "arm-first" approach presynthesized linear polymers are cross-linked using divinyl compounds. [14][15][16]49] A third strategy, "coupling onto", consist of attaching linear polymers onto a multifunctional core. The "arm-first" method is the most commonly used strategy to synthesize stars by the most popular CRP techniques (NMP, RAFT, and ATRP).…”
Section: Site Isolationmentioning
confidence: 99%
“…In the "corefirst" approach, polymeric arms are grown from a multifunctional cross-linked initiator, while in the "arm-first" approach presynthesized linear polymers are cross-linked using divinyl compounds. [14][15][16]49] A third strategy, "coupling onto", consist of attaching linear polymers onto a multifunctional core. The "arm-first" method is the most commonly used strategy to synthesize stars by the most popular CRP techniques (NMP, RAFT, and ATRP).…”
Section: Site Isolationmentioning
confidence: 99%
“…34−37 Regardless of the polymerization method used, the mechanism of star formation involves a balance of kinetically limited "star+star" and "star+linear" coupling reactions that ultimately defines the structure, size, and uniformity of the final star product. 38 In a pair of seminal reports, 34,35 Schrock and co-workers showed that addition of bis-olefin cross-linkers to living ROMP reactions led to poly(norbornene)-based star polymers with low polydispersities (PDIs) and ∼20−175 kDa molecular weights (MWs). This basic strategy has since been employed for the preparation of a wide array of functional materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As previous trials with grafting to approaches led to low functionalization of the hyperbranched template, and removal of unreacted amphiphilic double-shell building blocks turned out to be quite tedious, we decided to use the grafting-from approach. As already discussed in other publications, multiple hydroxyl groups on one branched scaffold allow the polymerization to simultaneously take place at ideally all accessible hydroxyl groups [23,24]. This concept of a so-called macroinitiator was used in our herein-presented work to polymerize ε-caprolactone in a tin-catalyzed ring opening polymerization.…”
Section: ε-Caprolactone Polymerization Using Hpes-oh 2 In Grafting Frommentioning
confidence: 83%
“…The initial PDI of 1.2 obtained after ultrafiltration was therefore decreased to 1.1. In addition to the impact of the purification, it is known and has been reported in the literature that the PDI of CMS nanocarriers is often lower than the PDI of the core or core-single shell precursors [24,27]. Owing to both the multistep synthesis and the extensive purification procedures, the overall yield was 12%.…”
Section: Synthesis Of Cms Nanocarriermentioning
confidence: 99%